A generic mechanism for finite-size coherent particle structures. (February 2019) - Romanò, Francesco; Wu, Haotian; Kuhlmann, Hendrik C.
Highlights: A non-inertial mechanism for a very rapid particle accumulation is found. The physics of the accumulation process is explained by identifying the source of dissipation responsible for the creation of particle-motion attractors. The particle-accumulation process is proven to be universal for a subclass of particle-laden flows. The general conditions under which the phenomenon occurs are clarified. Graphical abstract: Abstract: Particles transported by a fluid flow can accumulate in preferential regions. Usually, the clustering is caused by particle inertia, leading to inertial coherent particle structures. In the absence of inertia, particles can also cluster massively in a steady flow, solely owing to their size when they are repelled from a boundary by lubrication and lift forces. These forces can transfer the particles from the chaotic region to Kolmogorov–Arnold–Moser tori of the unperturbed incompressible flow, where they may focus on three-dimensional limit cycles. Numerical simulations for two different flow systems, taking into account the boundary-repulsion effect for finite-size particles, are in very good agreement with corresponding experiments. The results provide evidence that finite-size coherent particle structures are generic for a class of incompressible flows.